Strategic corporate social responsibility by a multinational firm - Constantine Manasakis; Evangelos Mitrokostas; Emmanuel Petrakis (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper investigates the determinants of a responsible multinational firm's decision to enter in a foreign country either through exports or through foreign direct investment (FDI), as well as the relevant market and societal outcomes. We find that CSR investments are higher under FDI than under exports. The multinational firm's incentives to serve the foreign country through FDI are increasing in the average consumer's valuation for CSR and in the intensity of the foreign country's market competition, but only if the average consumer's valuation for CSR in this country is sufficiently high. These incentives are mitigated by the multinational firm's liability in this country under exports. We also find that there is misalignment of preferences between the stakeholders of the two countries over the multinational firm's mode of entry in the foreign country.
Keywords: D43; F13; F23; 330; Corporate social responsibility; Multinational firms; Foreign direct investment; Exports; Import tariffs